Does EU Cohesion Policy Promote Growth? Evidence from Regional Data and Alternative Econometric Approaches - Philipp Mohl; Tobias Hagen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper analyses the growth e®ects of EU structural funds using a new panel dataset of 124 NUTS-1 / NUTS-2 regions over the time period 1995-2005. We extend the current literature with regard to at least three aspects: First of all, we extend the time period of investigation, using structural funds payments of the last Financial Perspective 20002006 that have not been analysed before. Second, we use more precise measures of structural funds by distinguishing between Objective 1, 2 and 3 payments and by investigating the impact of time lags more carefully. Third, we examine the robustness of our results by comparing different econometric approaches highlighting specific methodological problems. Apart from " panel data methods like system GMM, we apply spatial panel econometric techniques. The empirical evidence indicates that the Objective 1 payments in particular have a positive and significant impact on growth, whereas Objective 2 and 3 payments negatively affect the regions' growth rates. Furthermore, our results show that the growth impact occurs with a time lag of approximately two to three years.
Keywords: C21; O47; R11; R12; 330; EU structural funds; economic growth; spatial econometrics; EU-Strukturfonds; EU-Regionalfonds; Wirtschaftspolitische Wirkungsanalyse; Regionales Wachstum; Schätzung; EU-Staaten